Association between gap in spousal education and domestic violence in India and Bangladesh - Rapp Daniel; Zoch Beate; Khan M Mobarak H; Pollmann Thorsten; Krämer Alexander (BMC, 2012)
Abstract Background Domestic violence (DV) against women is a serious human rights abuse and well recognised global public health concern. The occurrence of DV is negatively associated with the educational level of spouses but studies dealing with educational discrepancies of spouses show contradicting results: Wives with higher education than their husbands were more likely to ever experience DV as compared to equally educated couples. The purpose of this study was to investigate the association between spousal education gap (SEG) and the prevalence and severity of DV in India and Bangladesh. Methods Nationally representative data collected through the 2005/2006 Indian National Family Health Survey (NFHS-3) and 2007 Bangladesh Demographic and Health Survey (BDHS) were used. In total, we analysed data of 69,805 women aged 15-49 years (Bangladesh: 4,195 women, India: 65,610 women). In addition to univariate and bivariable analyses, a multinomial logistic regression model was used to quantify the association between education gap and less severe as well as severe domestic violence. Adjustment was made for age, religion, and family structure. Results Wives with higher education than their husbands were less likely to experience less severe (OR = 0.83, 95% CI: 0.77-0.89) and severe (OR = 0.79, 95% CI: 0.72-0.87) DV as compared to equally low-educated spouses (reference group). Equally high-educated couples revealed the lowest likelihood of experiencing DV (severe violence: OR 0.43, CI 0.39-0.48; less severe violence: OR 0.59, CI 0.55-0.63). The model's goodness of fit was low (Nagelkerke's R2 = 0.152). Conclusions Our analysis revealed no increased DV among wives with a higher educational level than their husbands. Moreover, the results point towards a decrease of severe violence with an increase in education levels among spouses. However, the model did not explain a satisfying amount of DV. Therefore, further research should be done to reveal unknown determinants so that suitable interventions to reduce DV can be developed.